Self-Esteem, Positive Experience, Negative Experience, and Life Satisfaction University Students - Rahmania, Farra Anisa; Sari, Endah Puspita (Jurnal Psikologi Teori dan Terapan, 2024)
Background: Changes in a person's life from adolescence to adulthood are accompanied by experiences in college life. Self-esteem, positive and negative life experiences, and student life satisfaction can be interesting topics to study in more depth. Objective: The objective of this study is to identify the correlation between self-esteem, positive experiences, negative experiences, and life satisfaction in university students. Method: The study used The Rosenberg Self-Esteem Scale (RSES), Scale of Positive and Negative Experience (SPANE), and Satisfaction with Life Scale (SWLS). The data analysis used Spearman's correlation technique. Results: (1) There is a positive correlation between self-esteem and life satisfaction, (2) there is a positive correlation between positive experiences and life satisfaction, and (3) there is a negative correlation between negative experiences and life satisfaction. Conclusion: Based on the results of the study, it can be indicated that there is a correlation between self-esteem, positive experiences, negative experiences, and life satisfaction of university students.